Bio inspired nanocontainers: intracellular delivery and controlled cargo release - Kanika Arora; Sherilraj PM; Shyam Lal Mudavath (Nano Express)
Bio-inspired nanocontainers are versatile platforms for intracellular delivery and controlled release of therapeutic agents with unprecedented accuracy and efficiency. These systems harness diverse stimuli-responsive mechanisms that include pH-sensitive, enzyme-responsive, redox-sensitive, and external stimulus-controlled release strategies to deliver drugs and genes at specific physiological or pathological sites. Overcoming intracellular barriers such as endosomal entrapment by mechanisms like proton sponge effect, fusogenic peptides, and photochemical internalization is a critical factor in their success. Also, advanced surface functionalization allows organelle-specific targeting, leading to improved therapeutic outcomes in genetic disorders, cancer, and metabolic diseases. Multivalent targeting incorporated into bio-inspired nanocontainer systems is an innovative leap in intracellular delivery. Multivalent targeting allows for multiple interactions with cell surface receptors concurrently, thereby enhancing the binding affinity of nanocontainers to specific cell types and promoting receptor clustering coupled with downstream signal amplification. This approach allows for delivery that is highly selective, guaranteeing that therapeutic cargo has access to specific subcellular compartments such as the nucleus, mitochondria, or cytoplasm more precisely and efficiently. This paper presents an overview of the main mechanistic strategies that lead to these breakthroughs, which centers the design principles that allow stimuli-responsive behaviour and multivalency.